No room for culture? A brief review of cultural and urban planning in Hong Kong since the late 20th century - Hoi-lam Yiu, Melody (International Planning History Society Proceedings, 2024)
A cultural city is represented by its iconic cultural architecture, often attributed to the capacity for urban transformation vis-à-vis the legacy of Bilbao. However, cultural landmarks were conceived in urban development plans long before emerging on the architect’s drawing board. Meanwhile, advocacy in cultural support argues for the intrinsic value of culture, which has a greater social impact that cannot be measured by economic utility alone. This paper will discuss the planning of cultural facilities within the context of Hong Kong’s pronounced urban planning for economic growth, to unpack the sometimes-conflicting objectives between urban and cultural development. It will be done by mapping out key cultural projects since the post-war period and its intricate relationship with the major urban development plan. Although Hong Kong has never had a well-defined cultural policy, the piecemeal development of both landmark and district cultural facilities over the past decades has nonetheless constructed a rich depository of cultural resources. The establishment of the Culture, Sports, and Tourism Bureau (CSTB) in 2022 provides a timely occasion to review the trajectory of Hong Kong’s cultural development, from which this paper proposes to reconsider future cultural planning other than the mega-project developmental approach.